Didáctica de la educación física para la educación básica - Moreno Pinzón, Israel Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of the article is to present fundamental concepts and didactic bases of physical education that can be used in the educational field, related to the initial formation of the educators, and some key elements for the development of the subject of didactics of physical education for the Basic education of the students of the Bachelor in Basic Education who study at the pedagogical and technological university of Colombia with the Distance modality, elements that will serve as upda- ting and professional development in the exercise of teaching. Faced with teacher training, it is necessary to achieve a balance between discipli- nary training and mastery of didactic and pedagogical strategies to impart teaching, that is, to advance in the strengthening of didactic strategies for the design and execution of pedagogical practices in. The area of physical education. With respect to the diversity of student profiles there is a complexity, taking into account the wide variety of contexts where the teaching-learning processes are promoted. In this sense, the pertinence of the pedagogical accompaniment of the teachers who orient the subject, considering good planning and the staging of the processes of pedagogical intervention that the students of the degree are expected to develop.